Crop prices, farm incomes, and food security during the COVID-19 pandemic in India: Phone-based producer survey evidence from Haryana State - Ceballos, Francisco; Kannan, Samyuktha; Kramer, Berber (John Wiley & Sons, 2021)
In March 2020, India declared a nationwide lockdown in response to the COVID-19 pandemic. Such restrictions on mobility interrupted the normal functioning of agricultural value chains. For a sample of 1767 tomato and wheat producers in the state of Haryana, we study to what extent the lockdown limited access to inputs, labor, machinery, and markets to produce, harvest, and sell their crops. We quantify crop income reductions during the first months of the lockdown and analyze to what extent these are associated with borrowing and food insecurity. We find that wheat producers, for whom state-led procurement guaranteed market access at fixed prices, suffered minimal declines in income. For tomato producers—an already more vulnerable population—income fell by 50% relative to their expected income in a normal year, largely due to a steep fall of tomato prices as they shifted from wholesale markets to local retail markets, resulting in a sharp increase in local supply. Relative to wheat producers affected by the lockdown, reduced income for tomato producers was associated with an increase in borrowing and reduced food security. We conclude that targeting producers of crops that face substantial price risk and introducing policies that stabilize market prices are important in efforts to aid recovery and build resilience of smallholder farmers.